Education Management as Rationalization of Neoliberal Model (2014)
The article presents an analysis about conditions that made possible the radical transformation of the school administration, which involves passing from a responsible organizing discipline (subjects, spaces and tools) toward one that seeks to build moral codes of behavior, causing that new organizational school policies are appropriate for the subject as part of their own moral construction.